2018
DOI: 10.3390/genes9070337
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Analogue Treatment Primarily Induce miRNA Expression Changes and Up-Regulates Growth Inhibitory miR-7 and miR-148a in Neuroendocrine Cells

Abstract: Somatostatin (SST) analogues are used to control the proliferation and symptoms of neuroendocrine tumors (NETs). MicroRNAs (miRNA) are small non-coding RNAs that modulate posttranscriptional gene expression. We wanted to characterize the miRNAs operating under the control of SST to elucidate to what extent they mediate STT actions. NCI-H727 carcinoid cell line was treated with either a chimeric SST/dopamine analogue; a SST or dopamine analogue for proliferation assays and for identifying differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 69 publications
(81 reference statements)
1
17
0
Order By: Relevance
“…The already characterized and published miRNAs (except let-7c), however, did not play a role in the present study. Regarding let-7c, our results are supported by Døssing et al who recently have shown that SSA leads to an upregulation of let-7 family members [42], which inhibits the growth of carcinoid cell lines [31]. Therefore, the alterations seen in the present study may in part be induced by SSA treatment and adds further information in assessing the role of miRNAs in neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The already characterized and published miRNAs (except let-7c), however, did not play a role in the present study. Regarding let-7c, our results are supported by Døssing et al who recently have shown that SSA leads to an upregulation of let-7 family members [42], which inhibits the growth of carcinoid cell lines [31]. Therefore, the alterations seen in the present study may in part be induced by SSA treatment and adds further information in assessing the role of miRNAs in neuroendocrine tumors.…”
Section: Discussionsupporting
confidence: 87%
“…SSTR type-2 (SSTR2) is abundantly expressed on the surface of well-differentiated GEP-NETs [8, 42]. In this respect, in silico target gene analyses revealed that mir-185-3p directly interacts with SSTR2.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have determined the expression patterns of SSA-related miRNAs. Recently, Døssing et al identified distinct dysregulation of miRNAs, including miR-7 and miR-148a, in the human neuroendocrine tumor cell line NCI-H727 after treatment with SSA [ 15 ]. Another study revealed that circulating miR-200a is involved in metastasis during SSA-treated small intestine NET progression [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SSTRs are also expressed in human cancers, including GEP-NENs, with characteristic receptor profiles being described in certain tumors. However, the SSTR profiles vary considerably between tumor types and also between tumors of the same type, with 70-90% of GEP-NENs most frequently expressing SSTR2, followed by SSTR5 [22][23][24].…”
Section: Somatostatin and Somatostatin Analogs -An Overviewmentioning
confidence: 99%